Pemetaan Daerah Prioritas Penanganan Stunting Pada Ibu Hamil Menggunakan Metode Topsis - Nurfaidah .; Heliawaty Hamrul; Farid Wajidi (LPPM UNIBI, 2020)
West Sulawesi Province is one of the regions that have the second highest stunting rate in Indonesia based on records from the Ministry of Health since 2017. The cause of stunting is due to a lack of knowledge and self-awareness in paying attention to fetal nutrition levels for pregnant women, the role of the government in conducting counseling to areas they need in order to reduce the stunting rate, for this reason, a system has been created that can determine, which areas to prioritize in order to support the decision of the Health Office in selecting priority areas to be handled using the TOPSIS method. The TOPSIS method works by comparing each data as an alternative to the calculation criteria used, these criteria will be normalized first and weighted according to the level of importance of the existing criteria. The data used to fill in the criteria (pregnant women, unconsciousness of pregnant women, stunting, babies born, the estimated increase in stunting rate and distance) were obtained from the Majene District Health Office, which consisted of 11 community health center data as an alternative calculation. This system is website-based and the process of determining priority areas using the TOPSIS method is carried out directly on the website based on the data that has been collected and added to the website, then displayed through the geographic information system (GIS). The level of accuracy generated by the ranking that has been done is 81.81% by comparing the data obtained from the Majene District Health Office.